THE USE OF PQRST TECHNIQUE TO IMPROVE READING COMPREHENSION IN RECOUNT TEXT OF SECOND GRADE STUDENTS OF MTsN KEDIRI 1 - fikri, muhammad alwi (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 2 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
This study was aimed to find out the use of PQRST technique on studentsâ€™ reading comprehension. It concern with the improvement of the students  in reading comprehension through the implementation of PQRST technique. The design of this research is qualitative while   Classroom Action Research (CAR) as approach. This research was conducted in the second semester of  Islamic Nation of junior High School (MTsN) Kediri 1 in academic year 2016/2017. The students were 27 students. It consists of 21 female students and 6 male students. To  know the result of students activity , the researcher used observation checklist, field note, questionnaire, and interview. Meanwhile, to know the improvement of reading comprehension, the researcher used test. From ideal score 78, average score increased become 91,55. The score was increased from 76,41 in cycle one became 91,55 in cycle two. The indicator of classroom was success was 85%. In the first cycle, the class percentage was 62,96%. So, teaching and learning process by PQRST technique in reading Recount text was success. This technique was useful for the students in their reading comprehension.